Profiling Thermus thermophilus Argonaute Guide DNA Sequence Preferences by Functional Screening - Hunt, Eric A.; Tamanaha, Esta; Bonanno, Kevin; Cantor, Eric J.; Tanner, Nathan A. (Frontiers in Molecular Biosciences, 2021)
Prokaryotic argonautes are an increasingly well-studied class of guided endonucleases, and the underlying mechanisms by which prokaryotic argonautes generate nucleic acid guides in vivo remains an important topic of investigation. Recent insights into these mechanisms for the argonaute from Thermus thermophilus has drawn attention to global sequence and structural feature preferences involved in oligonucleotide guide selection. In this work, we approach the study of guide sequence preferences in Thermus thermophilus argonaute from a functional perspective. Screening a library of 1,968 guides against randomized single- and double-stranded DNA substrates, endonuclease activity associated with each guide was quantified using high-throughput capillary electrophoresis, and localized sequence preferences were identified which can be used to improve guide design for molecular applications. The most notable preferences include: a strong cleavage enhancement from a first position dT independent of target sequence; a significant decrease in activity with dA at position 12; and an impact of GC dinucleotides at positions 10 and 11. While this method has been useful in characterizing unique preferences of Thermus thermophilus argonaute and criteria for creating efficient guides, it could be expanded further to rapidly characterize more recent mesophilic variants reported in the literature and drive their utility toward molecular tools in biology and genome editing applications.